Selection of Bread Wheat for Low Grain Cadmium Concentration at the Seedling Stage Using Hydroponics versus Molecular Markers. Issue 3 (1st May 2019) - Liu, Caixia; Guttieri, Mary J.; Waters, Brian M.; Eskridge, Kent M.; Baenziger, P. Stephen
Abstract : The excessive accumulation of Cd in harvested crops grown on high‐Cd soils has increased public concerns for food safety. Due to the high consumption of bread wheat ( Triticum aestivum L.) per capita, high concentrations of Cd in wheat grain can significantly affect human health. Breeding is a promising way to reduce grain Cd concentration. However, a lack of efficient selection methods impedes breeding for low grain Cd concentration in bread wheat. In this study, a recombinant inbred population segregating for grain Cd concentration was used to assess the efficacy of two selection methods for decreasing grain Cd concentration in bread wheat: a hydroponic selection method used shoot Cd concentration in 2‐wk‐old seedlings growing in Cd‐containing medium, and a marker‐based selection method using markers linked to heavy metal transporting P1B‐ATPase 3 ( HMA3 ), the gene underlying Cdu1. Both methods effectively selected low‐Cd lines. The HMA3 ‐linked marker‐based selection was superior to hydroponic selection in terms of both simplicity and response to selection. The HMA3 ‐linked markers explained 20% of the phenotypic variation in grain Cd concentration with an additive effect of 0.014 mg kg −1 . The hydroponic selection and marker‐based selection may target two different and independent processes controlling grain Cd accumulation, and they had no effect on grain Zn and Fe concentrations. The ALMT1‐UPS4 marker associated with Al tolerance was not associated with grain Cd concentration but increased grain Zn and Fe concentrations. The 193‐bp allele of the Rht8 ‐associated marker, GWM261, was associated with increased grain Cd concentration.